News-Based Uncertainty and Macro-Market Fusion for VIX Direction Forecasting: Evidence from 2015-2024 FRED Panel - Hailin Zhou; Kai Zhang (Journal of Technology Informatics and Engineering, 2025)
This paper evaluates news-based uncertainty and macro-market fusion for one-trading-day VIX direction forecasting using a 2015-2024 daily FRED panel. The dependent variable equals one when the next trading-day VIX close exceeds the current close. The final panel contains 2,512 processed observations from 2015-02-04 to 2024-12-30, with 1,997 training observations from 2015-2022, 257 validation observations in 2023, and 258 holdout observations in 2024. The feature set combines VIX market-state variables, the daily newspaper-based Economic Policy Uncertainty index, the effective federal funds rate, 10-year and 2-year Treasury yields, lagged CPI inflation, lagged unemployment, and interaction terms. Expanding cross-validation on the 2015-2022 training sample gives the highest average ROC AUC to Fusion Random Forest (0.5620). The 2023 validation window selects a weighted fusion ensemble with ROC AUC 0.6005; its weights are fixed before the 2024 test. In the 2024 holdout window, VIX-only Logistic achieves the highest one-day ROC AUC (0.5869) and F1 (0.5448), while the weighted fusion ensemble reaches ROC AUC 0.5638 and F1 0.4786. Event-window diagnostics show that EPU shocks following calm VIX states have a next-day VIX-up rate of 0.5672, compared with 0.4445 on other trading days. The findings support a cautious interpretation: news-based uncertainty contains conditional information, but one-day practical forecasting reliability remains modest and VIX state variables remain the strongest 2024 holdout benchmark.